2022
DOI: 10.3389/fncel.2022.808598
|View full text |Cite
|
Sign up to set email alerts
|

Microglia-Specific Promoter Activities of HEXB Gene

Abstract: Adeno-associated virus (AAV)-mediated genetic targeting of microglia remains a challenge. Overcoming this hurdle is essential for gene editing in the central nervous system (CNS). Here, we characterized the minimal/native promoter of the HEXB gene, which is known to be specifically and stably expressed in the microglia during homeostatic and pathological conditions. Dual reporter and serial deletion assays identified the critical role of the natural 5’ untranslated region (−97 bp related to the first ATG) in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 33 publications
(54 reference statements)
0
3
0
Order By: Relevance
“…Although HEXB immunostaining has been utilized in combination with TMEM119 to directly identify microglia ( Jia et al, 2021 ), Hexb -based gene reporter and fate mapping tools, have also recently provided important insights into the behavior and functions of microglia in vivo ( Masuda et al, 2020 ). Additionally, the promoter region of Hexb has recently been characterized, enabling the study of Hexb as a potential target for microglia-targeted gene therapies in humans ( Shah et al, 2022 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
See 1 more Smart Citation
“…Although HEXB immunostaining has been utilized in combination with TMEM119 to directly identify microglia ( Jia et al, 2021 ), Hexb -based gene reporter and fate mapping tools, have also recently provided important insights into the behavior and functions of microglia in vivo ( Masuda et al, 2020 ). Additionally, the promoter region of Hexb has recently been characterized, enabling the study of Hexb as a potential target for microglia-targeted gene therapies in humans ( Shah et al, 2022 ).…”
Section: Antibody-mediated Identification Of Microglial Markersmentioning
confidence: 99%
“…Recent studies using RNAscope and single-cell RNA sequencing have shown that Hexb is expressed in brain microglia and its expression is highly restricted to these cells within the CNS (Masuda et al, 2020;Faust et al, 2023). Notably, it was not detected in CNS-associated macrophages according to Masuda et al (2020); however, it has been identified in non-CNS cells, such as Ly6C + monocytes obtained from the bone marrow (Hickman et al, 2013;Monaghan et al, 2019;Masuda et al, 2020;Shah et al, 2022). HEXB may also play a role in pathology, with elevated gene expression of HEXB associated with poor prognosis in human glioblastoma (Jia et al, 2021).…”
Section: Intracellular Proteins and Transcriptional Factorsmentioning
confidence: 99%
“…To evaluate the activation status of innate immune cells in PD model mice, we rst examined the resident and in ltrating Mo/MΦs in the SNpc. Recent massive single-cell analyses revealed that Hexb is exclusively expressed in brain microglia but not in Mo/MΦs [37,40]. Importantly, this newly de ned microglia-speci c gene identi ed Hexb as a stably expressed microglial core gene during homeostasis and disease, Iba1 is a calcium-binding protein both expressed in microglia and Mo/MΦs.…”
Section: Mptp Administration Causes Dopaminergic Neuron Injury In The...mentioning
confidence: 99%
“…Similarly, Hexb is a lysosomal enzyme that play critical role in lysis processes, breaking down fatty compounds such as sphingolipids and gangliosides (Kuil et al, 2019). Recent studies using RNAscope and single-cell RNA sequencing have shown that Hexb is exclusively expressed in brain microglia but not in monocytes/macrophages across homeostasis and pathological conditions in mice (Hickman et al, 2013;Masuda et al, 2020;Shah et al, 2022). HEXB may also play a role in pathology, with elevated gene expression of HEXB associated with poor prognosis in human gliobastoma (Jia et al, 2021).…”
Section: Intracellular Proteinsmentioning
confidence: 99%
“…Although HEXB immunostaining has been utilized in combination with TMEM119 to directly identify microglia (Jia et al, 2021), Hexb-based gene reporter and fate mapping tools, have also recently provided important insights into the behavior and functions of microglia in vivo (Masuda et al, 2020) (discussed below). Additionally, the promoter region of Hexb has recently been characterized, enabling the study of Hexb as a potential target for microglia-targeted gene therapies in humans (Shah et al, 2022).…”
Section: Intracellular Proteinsmentioning
confidence: 99%